The effects of prophylactic use of paracetamol on body temperature and blood pressure in elderly patients with acute stroke: Data from the PRECIOUS trial - Jeroen C. de Jonge; Wouter M. Sluis; Hendrik Reinink; Philip Bath; Lisa J Woodhouse; Diederik van de Beek; Anne Hege Aamodt; Alfonso Ciccone; Janika Kõrv; Iwona Kurkowska-Jastrzebska; Milani Deb-Chatterji; Jesse Dawson; et al. (PLoS ONE, 2026)
Background and aims Prophylactic administration of paracetamol (acetaminophen) has been reported to reduce body temperature in the first day after stroke and to reduce blood pressure on the first day. We aimed to validate these findings in the randomised PRECIOUS trial and to assess the effect of paracetamol on body temperature in the first seven days after stroke. Patients and methods PRECIOUS was an international, 3*2 factorial, randomised, controlled, clinical trial assessing preventive treatment with paracetamol, metoclopramide, and ceftriaxone in patients aged 66 years or older with acute stroke and a score on the National Institutes of Health Stroke Scale (NIHSS) ≥ 6. Paracetamol was given in a dose of 4g daily for four days. Vital signs were recorded at 12 hours intervals up to seven days. The primary outcomes of this study were body temperature and systolic and diastolic blood pressure at 24 hours after randomisation, analysed with linear regression. The presence of a subfebrile temperature or fever at 24 hours was a secondary outcome. Results We used data from 1419 of 1493 patients included in PRECIOUS. Paracetamol reduced mean body temperature by 0.1°C (95% CI, 0.0–0.2) at 24 hours after randomisation but did not lower systolic or diastolic blood pressure. Paracetamol reduced the occurrence of subfebrile temperatures or fever at 24 hours from 15.8% to 8.3% (p < 0.001). The effects of paracetamol on body temperature were consistent over the four days of treatment. Conclusion Prophylactic use of paracetamol resulted in a modest reduction in mean body temperature and almost halved the rate of subfebrile temperatures or fever at 24 hours after stroke, but had no effect on blood pressure.